2018
DOI: 10.4066/biomedicalresearch.29-18-618
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of drug-drug interactions and polypharmacy among elderly patients in Jordan

Abstract: Background: The number of people aged 60 or older is estimated to be 5.6% among Jordanian population, those elderly people need special medical care; since they have a greater prevalence of chronic diseases and therefore subjected to higher prevalence of polypharmacy and potential drug-drug interaction (pDDI). There is no data about polypharmacy and pDDI in elderly patients among the Jordanian population. Methods: Prescriptions for patients aged 60 or older were examined and those patients were interviewed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
4
19
1
1
Order By: Relevance
“…This result may attributed to low pharmaceutical care interventions, physicians poor adherence to the guidelines, and absence of clinical decision support system in the operated computerized physician order entry system (CPOE) . Our findings are in line with other studies in Jordan that indicated high rate of DDIs and poor adherence to the guidelines by physicians (21,22,27). The difference between the recent studies in Jordan and our study is that the patient group in our research is highly vulnerable to severe deadly complications, and thus urgent precautionary measures are necessary.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result may attributed to low pharmaceutical care interventions, physicians poor adherence to the guidelines, and absence of clinical decision support system in the operated computerized physician order entry system (CPOE) . Our findings are in line with other studies in Jordan that indicated high rate of DDIs and poor adherence to the guidelines by physicians (21,22,27). The difference between the recent studies in Jordan and our study is that the patient group in our research is highly vulnerable to severe deadly complications, and thus urgent precautionary measures are necessary.…”
Section: Discussionsupporting
confidence: 89%
“…Physicians in Jordan demonstrated poor adherence to current practice guidelines for safe prescription of antibiotics (20)(21)(22)(23), proton pump inhibitors (24,25), and non-steroidal antiinflammatory drugs (26). In addition, high rate of major and moderate drug-drug interactions was found among elderly patients in Jordan (27). As a possible solution, clinical pharmacists in Jordan exhibited the ability to identify and intervene on such inappropriate prescriptions (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Various pharmacoepidemiological studies conducted in the different parts of the world in various study settings, study design, duration, and diverse population and with various DDI assessment tools have reported the prevalence rates of pDDIs, varying from 5% to 91%. [ 9 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of polypharmacy in the Middle East was reported to be between 44.8 and 96% in different practice settings . In Jordan, 44.8–72.9% of elderly patients were found to have polypharmacy . Polypharmacy effects are not limited to elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported that around half (47.5%) of the adults at outpatients clinics have polypharmacy . Consequently, 91–96% of polypharmacy patients in Jordan had at least one potential drug–drug interaction . Moreover, 27.7% of adult patients in Jordan were found to have unnecessary drug therapy.…”
Section: Introductionmentioning
confidence: 99%